Distribution Mechanism of Subsidies Fertilizer on Rice Farmers in Baruga Sub-District Kendari City - Harnas, Sitti; Batoa, Hartina; Mardin, Mardin; Djayadisastra, Yoenita (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Effectiveness of the Distribution of Subsidized Fertilizers to Rice Paddy Farmers in Baruga Village, Baruga sub-District, Kendari City. This research objectives were to determine the mechanism of distribution of subsidized fertilizers on rice paddy farmers in Baruga village Baruga Sub-district, Kendari. This research was conducted in the Baruga Sub-District of Kendari from November 2019 until January 2020. The method of sampling research used is the research method to answer the goal is to use a descriptive analysis used to describe the distribution mechanisms of subsidized fertilizers on rice farmers and quantitative analysis using a systematic formula to know The effectiveness of the distribution of subsidized fertilizers on rice paddy farmers in Baruga village, Baruga sub-district, Kendari City. The results showed that the distribution mechanism of subsidized fertilizers on rice paddy farmers was following the distribution flow according to government regulations. Still, in part, Pengantongan Unit fertilizer does not do its job with the full IE must Label the fertilizer sack with the label "subsidized fertilizer, so as not to be sold to other parties with a higher price for the individuals in firmness and profit.